Enabling reciprocity through blockchain design - Jens Gudmundsson; Jens Leth Hougaard (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2020)
We introduce a reciprocity protocol, an innovative approach to coordinating and sharing rewards in blockchains. Inherently decentralized and easy to implement, it puts emphasis on incentives rather than forcing specific sharing rules from the outset. Analyzing the non-cooperative game the protocol induces, we identify a robust, strict, and Pareto-dominant symmetric equilibrium. In it, even self-centered participants show extensive reciprocity to one another. Thus, despite a setting that is generally unfavorable to reciprocal behavior, the protocol manages to build trust between the users by taking on a role akin to a social contract.
Keywords: C62; C72; D02; D63; D91; 330; Blockchain; reciprocity; protocol design; Nash equilibrium